2013
DOI: 10.1108/02652321311298627
|View full text |Cite
|
Sign up to set email alerts
|

Islamic banks

Abstract: Purpose -The purpose of this study is to investigate customer satisfaction and its effect on image, trust, and customer loyalty for Islamic banks. Design/methodology/approach -The study uses data from Islamic banks and dual-window Islamic banks, pertaining to two different customer segments (Muslims and non-Muslims). Findings -The results indicate that customer satisfaction has a significant relationship with image, image has a significant relationship with trust, and trust has a significant relationship with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
99
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(116 citation statements)
references
References 72 publications
12
99
0
5
Order By: Relevance
“…With the value of CR = 5.582> t-table = 1.96 or p = 0.000 <Î ± = 0.05, the null hypothesis is rejected, and the alternative hypothesis is accepted, so it can be concluded that the Customer Relations has a significant effect on Customer Loyalty. This finding was corroborated by Amin et al (2013) Anabila and Awunyo-Vitor (2013) and Quoquab et al (2014) who found that Customer Relations had a significant influence on Customer Loyalty.…”
Section: Figure 1 Research Modelmentioning
confidence: 57%
See 2 more Smart Citations
“…With the value of CR = 5.582> t-table = 1.96 or p = 0.000 <Î ± = 0.05, the null hypothesis is rejected, and the alternative hypothesis is accepted, so it can be concluded that the Customer Relations has a significant effect on Customer Loyalty. This finding was corroborated by Amin et al (2013) Anabila and Awunyo-Vitor (2013) and Quoquab et al (2014) who found that Customer Relations had a significant influence on Customer Loyalty.…”
Section: Figure 1 Research Modelmentioning
confidence: 57%
“…The magnitude of the influence of the Bank's image on Customer Loyalty 11.90%, with a CR value of 5.417 and a p-value of 0,000 CR value of 5.417> t-table = 1.96 or an amount of p = 0,000 <Î ± = 0.05 then the null hypothesis is rejected, and alternative hypotheses are accepted, so it can be concluded that Brand Image has a significant influence on Customer Loyalty. (Amin et al, 2013;Anabila and Awunyo-Vitor, 2013;Quoquab et al, 2014) found that the Bank's image had a significant influence on customer loyalty. The Bank's image has the most significant influence compared to other variables on customer loyalty, which is 11.9%.…”
Section: Figure 1 Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists claim that there is a direct relationship between the image of commercial banks and customers' trust (Amin et al 2013;Skvarciany, Iljins 2015). There are scientists who state that bank's reputation is the factor that could increase the level of customers' trust (Debab, Yateem 2012;Gul 2014).…”
Section: Factors Influencing Trust In Traditional Bankingmentioning
confidence: 99%
“…Thus, Islamic banking is favored by Muslim consumers compared to consumers from of other religion as it helps them to fulfil their requirements to follow the Sharia law in business and transactions. However, there is also a good probability for the growth in percentage of non-Muslim customers in Islamic banking if the benefits are made apparent to them, which will help in the internationalization of Islamic banks (Amin, Isa, Fontaine, 2013). Thus, Islamic banks have to disseminate knowledge about Islamic banking to the public using a more competent system and also create better brand image to achieve a larger market share.…”
Section: Introductionmentioning
confidence: 99%